A novel detonation arrester containing a large disk with long triangular slits: Design and numerical simulation. Issue 1 (29th July 2020) - Yue, Jianping; Long, Wei; Liu, Huaguo; Guo, Shuaishuai
Abstract: Aiming at the problem that common flame arresters can only extinguish deflagration flame, but cannot effectively extinguish detonation flame in large pipelines, this paper proposes a novel structure of detonation arrester based on heat transfer theory to improve the detonation flame extinguishing efficiency. The flame arresting element is composed of a large disk with long triangular slits and is used as the quenching part of detonation arrester in a monolithic structure. Compared with common flame arrester consists of several small fires retarding elements, the proposed monolithic structure is safer due to its integrity. In addition, this paper explores the relationship between flame extinguishing ability, detonation pressure, and temperature change. This investigation determined that the diameter of the quenching part and the parameters(length and height) of the long triangular slits were the key factors affecting the quenching characteristics, and as the diameter and porosity increase, the detonation pressure at the front of the flame arrester will decrease. Finally, the rationality and applicability of the structure are verified by simulation experiments. These preliminary conclusions are helpful to reveal the nature of the proposed structure and solve the technical problem of preventing detonation flame propagation of coal mine gas in large pipelines.